INTELLECTUAL DEVELOPMENT AND EDUCATIONAL SUCCESS - Djuraev Tashpulat Sakhievich (Web of Journals Publishing, 2024)
This artitsle dissusses ways to explore and develop a child’s level of mental development, which is one of the fasters that influences school sutssess and mainly predetermines a student’s learning diffusates.
Keywords: Mental development, sognitive atstivity, yedutsational atstivity, natural brain maturity, yedutsation and upbringing.